The fate of flavanol-anthocyanin adducts in wines: Study of their putative reaction patterns in the presence of acetaldehyde - Frederico Nave (2010)
Methylmethine bridged flavanol-anthocyanin dimeric adducts (F-A) were synthesised by hemisynthesis using catechin, acetaldehyde and F-A adducts as precursors in order to simulate putative reactions undergoing in red wine. The products obtained, catechin-methylmethine-catechin-malvidin-3-O-glucose and methylmethine-(catechin-malvidin-3-O-glucose), were analysed by HPLC-ESI-MS. The fragmentation patterns allowed the confirmation of the structures. These compounds were investigated and found in wine samples (2-year-old table wine and 10-year-old Port wine), thus confirming their formation in vino as a result of flavanol-anthocyanin adducts transformations.